Developing Computational Thinking Ability in Early Childhood Education: The Influence of Programming-toy on Parent-Children Engagement - Cucuk Wawan Budiyanto; Faaizah Shahbodin; Muhammad Ulin Khoirul Umam; Ratih Isnaini; Anayanti Rahmawati; Indah Widiastuti (International Journal of Pedagogy and Teacher Education, 2021)
Technology and smart devices have become ubiquitous staples in every aspect of human life. Given the rise of computation in everyday life, introducing technology to early childhood students requires exposure to logical thinking and problem-solving skills through programming approaches or computational thinking. This research addresses an inquiry into a comprehensive elaboration of the development of early childhood computational thinking. A novel programming toy was introduced as an educational tool based on designated themes in accordance with early childhood education curricula. Five stages were conducted to reveal parental and child engagement in robotics activities and later, interviews were conducted on children’s cognitive development from the parent's perspective. Children were observed exploring in various ways by concentrating and paying attention, doing the given activities and expressing their excitement and happiness. The notion that children learn from their social network environment was highlighted by the way in which the children involved in the KARIN programming toy’s hands-on activities were driven to be more actively engaged in the exercise. In addition to parent-student engagement, the use of the KARIN programming toy helps to shed light on how students in early childhood learn while away from their social relations during a pandemic.